Danggui Shaoyao San attenuates depressive-like behaviors in mice via TLR4/NF-κB p65/JAK-STAT3/AKT-GSK3β signaling pathways: modulation of hippocampal neurogenesis and neuroinflammation - Tang, Chuan-Feng; Li, Fan; Ma, Lu-Han; Wang, Qiao-Na; Xie, Peng-Fei; Xiang, Lang; Zhu, Yu-Jie; Wang, Yue-Yao; Zhang, Yi-Zhu; Shi, Jun-Jie; Li, Sheng-Jie; Li, Jian-Mei (Frontiers in Nutrition, 2025)
PurposeDanggui Shaoyao San (DSS), a traditional Chinese herbal formula abundantly containing both medicinal and dietary components, was first documented in Jin Gui Yao Lue (Synopsis of the Golden Chamber) by Zhang Zhongjing during the Eastern Han Dynasty of China. Depression, a multifactorially induced affective disorder, has its precise etiological factors and underlying pathophysiological mechanisms remaining incompletely understood. Therefore, this study aimed to investigate the therapeutic effects of DSS on corticosterone-induced depression in mice and clarify the underlying mechanisms.MethodsThe therapeutic effects of DSS on depressive-like behaviors were assessed via behavioral tests in mice. Potential therapeutic targets of DSS were explored via network pharmacology and RNA sequencing (RNA-seq) approaches. Furthermore, immunofluorescence staining was utilized to evaluate neuroinflammatory responses and hippocampal neurogenesis. Additionally, Western blot analysis was performed to verify the molecular mechanisms underlying DSS-mediated alleviation of depressive-like behaviors in mice.ResultsNetwork pharmacology analysis revealed 12 phytochemical constituents targeting 168 depression-associated genes. RNA-seq and immunofluorescence staining analyses demonstrated that DSS attenuates hippocampal neuroinflammation via suppressing microglial activation and enhances hippocampal neurogenesis by restoring the number of neural stem cells (NSCs). At the mechanistic level, DSS mitigates depressive-like behaviors in mice through coordinated modulation of the TLR4/NF-κB p65, JAK2/STAT3, and AKT-GSK3β signaling pathways. Collectively, these results position DSS as a potential adjuvant intervention that concurrently modulates both neuroinflammatory responses and hippocampal neurogenesis in depression.ConclusionCollectively, our study deciphers the anti-depressant mechanisms of DSS via TLR4/NF-κB p65, JAK2/STAT3 and AKT-GSK3β signaling pathways, while establishing a drug development paradigm that bridges ethnopharmacology and modern systems biology. This integration offers a blueprint for exploiting traditional medicines in CNS drug discovery.